Analysis factors that influence prenatal stress levels and the impact of preparation on labour and delivery - Anisrina Anisrina; Maidar Maidar; Hermansyah Hermansyah; Meutia Zahara; Asnawi Abdullah (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Pregnancy is a crucial period that significantly influences both the physical and psychological well-being of mothers. One of the most common health concerns during pregnancy is the mother's mental health, which can influence both her weight gain and the estimated weight of the fetus. Purpose: To identify the factors that influence prenatal stress levels and the impact of preparation on labour and delivery. Method: This cross-sectional study involved 120 third-trimester pregnant women, recruited using a total sampling technique. Data were obtained through questionnaire-based interviews and analyzed using ordinal logistic regression. Results: Mild stress levels was experienced by 63.33% of participants. Variables associated with prenatal stress included maternal age, education, income, occupation, social support, pregnancy complications, pregnancy status, antenatal care (ANC) visits, and parity. Prenatal stress was found to influence both maternal weight gain and estimated fetal weight. Conclusion: Maternal age and parity were identified as protective factors against prenatal stress. The multivariate model accounted for 63% of the variation in mental health observed.